2022
DOI: 10.1177/10668969221142038
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-Fetoprotein (AFP)-Negative Hepatoid Adenocarcinoma of the Stomach and its Associated Uncommon Features With a Review

Abstract: Hepatoid adenocarcinoma of the stomach is a rare histologic subtype of gastric carcinoma. Morphologically, it shows hepatocyte-like features and the tumor cells can show the expression of alpha-fetoprotein (AFP) in the tumor cells as well as in serum. There are a few AFP-negative hepatoid adenocarcinoma tumors that have been reported in the literature. A 45-year-old male patient presented with abdominal pain. Endoscopy and radiological studies showed an ulceronodular thickening in the antropyloric thickening w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Subsequently, Ishikura ( 5 ) reported an instance of primary GA characterized by markedly elevated AFP levels (12,000 ng/ml), coining the term HAS. Subsequent investigations established that HAS may also manifest without elevated AFP levels ( 6 ), suggesting that elevated serum AFP serves as a hallmark of HAS but lacks absolute specificity. HAS is distinguished by its aggressive behavior and dismal prognosis in comparison to GA and HCC ( 3 , 7 9 ), with median survival ranging from 10 months to 18 months ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, Ishikura ( 5 ) reported an instance of primary GA characterized by markedly elevated AFP levels (12,000 ng/ml), coining the term HAS. Subsequent investigations established that HAS may also manifest without elevated AFP levels ( 6 ), suggesting that elevated serum AFP serves as a hallmark of HAS but lacks absolute specificity. HAS is distinguished by its aggressive behavior and dismal prognosis in comparison to GA and HCC ( 3 , 7 9 ), with median survival ranging from 10 months to 18 months ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…They also concluded that IHC and serum AFP levels are important to the diagnosis of HAS. There are already several studies regarding how serum AFP can improve the accuracy of diagnosis [ 8 , 9 ]. However, due to the rarity of HAS, the IHC and Epstein–Barr virus‐encoded small RNA (EBER) features of HAS have not been fully acknowledged [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are already several studies regarding how serum AFP can improve the accuracy of diagnosis [ 8 , 9 ]. However, due to the rarity of HAS, the IHC and Epstein–Barr virus‐encoded small RNA (EBER) features of HAS have not been fully acknowledged [ 9 , 10 ]. According to previous research, HAS presents distinctive traits such as negativity for EBER, predominance of microsatellite stability (MSS), and high human epidermal growth factor receptor 2 (HER2) positive rate [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%